The problem can be solve using the equation of law of gravity:
F = G(m1 m2)/r^2
Whre G = gravitational constant = 6.674×10−11 N · (m/kg)^2)
F is the force between the masses
m1 is the first mass (person)
m2 is the second mass (earth) = 5.98 × 10^24 kg
r is the distance between the centers of the masses
convert the given value to si units
3960 + 1840 mi = 5800 mi = 9334195 m
185 lb = 83.9146 kg
F = (6.674×10−11 N · (m/kg)^2) *(83.9146 kg)*( 5.98 × 10^24 kg)/( 9334195 m)^2
F = 9.22x10^-21 N
M = 9.22x10^-21 N/9.81m/s2 =9.40x10^-22 kg